The Balance between Orthodontic Force and Radiation in the Jawbone: Microstructural, Histological, and Molecular Study in a Rat Model - Hadas Dorchin-Ashkenazi; Ravit Ginat-Koton; Yankel Gabet; Yehuda Klein; Stella Chaushu; Hezi Dorchin; Tamar Brosh; Marilena Vered (Biology, 2021)
Irradiation of facial bones is associated with a lifelong risk of osteonecrosis. In a rat model, maxillae were exposed to a single 5 Gy dose of external beam radiation and orthodontic force was applied for 2 weeks on the first maxillary molar; control rats were treated identically without radiation. Tooth movement in irradiated jaws was 30% less than in controls, representing radiation-related damage. Micro-CT, histological, and molecular outcomes of orthodontic tooth movement were studied. Microstructurally, bone parameters (trabecular thickness, bone volume fraction, bone mineral density) were significantly affected by orthodontic force but not by radiation. Histological parameters were influenced only by orthodontic force, especially by an increase in osteoclasts. A molecular study revealed a differential distribution of cells expressing pre-osteoclast markers (RANK+—majority, CD11b+, CD14+—minority), with changes being influenced by orthodontic force (increased CD11b+ and CD14+ cells) and also by radiation (decreased RANK+ cells). The activation status of osteoclasts (TRAP staining) showed an orthodontic-force-related increase, which probably could not fully compensate for the radiation-associated impairment. The overall balance showed that orthodontic force had elicited a substantial microstructural, histological, and functional normalization process in irradiated maxillae but a radiation-induced impact was still conspicuous. Additional studies are needed to validate these findings.